2008
DOI: 10.1007/s00038-007-6019-8
|View full text |Cite
|
Sign up to set email alerts
|

Absence of protein-energy malnutrition in Prague homeless

Abstract: The data fails to demonstrate the existence of protein-energy malnutrition in Prague's homeless population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…A *1 kg increase is also lower than observed after 12 weeks of soccer training for untrained men (1.7 kg) (Krustrup et al 2009) and in contrast to a previous study by Krustrup et al (2010b) no increase in quadriceps muscle mass was observed. Some (Darmon et al 2001) but not all (Kubisova et al 2008) studies have reported malnutrition in homeless men, and a questionnaire that was filled out by nine of subjects in the present study showed an average protein intake of 74% of recommended daily intake. However, further studies are required to establish whether diet-manipulation may lead to a more pronounced muscle hypertrophy after short-term training for the homeless.…”
Section: Discussioncontrasting
confidence: 47%
“…A *1 kg increase is also lower than observed after 12 weeks of soccer training for untrained men (1.7 kg) (Krustrup et al 2009) and in contrast to a previous study by Krustrup et al (2010b) no increase in quadriceps muscle mass was observed. Some (Darmon et al 2001) but not all (Kubisova et al 2008) studies have reported malnutrition in homeless men, and a questionnaire that was filled out by nine of subjects in the present study showed an average protein intake of 74% of recommended daily intake. However, further studies are required to establish whether diet-manipulation may lead to a more pronounced muscle hypertrophy after short-term training for the homeless.…”
Section: Discussioncontrasting
confidence: 47%
“…Age of the participants was more or less the same across the studies, ranging from 19 to 76 years with an average of 46 years (IQR 43.25–48.75). Participants recruited were either from the streets (rough sleepers) [17, 18, 21, 23, 24], or from shelters and clinics [13, 16, 18, 22]. When reported, [18, 21], the duration of homelessness varied greatly, ranging between one month to 55 years among the participants.…”
Section: Resultsmentioning
confidence: 99%
“…B9 and B12 = isotopic radioassay; C = colorimetric procedure using dinitrophenylhydrazine.van der Westhuyzen 1987 [22]Blood levels of: B6; B9; B12; albumin; erythrocyte level of B1Reference ranges determined in healthy subjects: B6 = 26–96 nmol/; B1 = 50–106 microgram/liter; B12 = 160–900 ng/l; serum folate = 2–13microgram/liter; serum I'-glutamyltransferase (GGT) = 10–50 U/I.Radio-assay kit; Biochromatic Analyzer commercial kits; For B1 = automated microbiological assay using a streptomycin-resistant mutant of Lactobacillus fermenci as the test organism.Drijver 1993 [16]TDP effect and TK activity for B1; Blood levels of: B6; B12TDP effect reference range = 0–25%; TK activity reference range = 10.4–15.1 U/mmol Hb; PLP effect reference range = 35–107 nmol/l;HPLC; PLP measured with a fluorimeterKertesz 2001 [24]Levels NR. Results of the following were found normal: B12; B 9; ironNRHospital testsMalmauret 2002 [21]Blood levels of vitamins: A; B1; B6; B9; B12; C; EB6 = 23–100 nmol/l; B12 = 160–420 pmol/l; B1 = 6–40 mmol/l.HPLC and radioimmunoassayFung 2005 [23]Anaemia, albumin levelNRNRKubisova 2008 [18]Blood levels of: prealbumin; albumin; haemoglobinAlbumin <33 g/l; prealbumin <0.16 g/l.NRLee 2014 [20]Blood levels of: B1; B6; B12; C; haemoglobinReference ranges for vitamins: B1 = 59 to 213; B12 = 200 to 950; B6 = 20 to 202; C = 26.1 to 84.6Vitamin B1, B6, and C = HPLC; B12 levels = electro-chemiluminescence immunoassay A Retinol/beta carotene, B1 thiamine, B2 riboflavin, B3 niacin, B5 pantothenic acid, B6 pyridoxine, B7 biotin, B9 folic acid, B12 cobalamins, C ascorbic acid, D ergo/cholecalciferol, E tocopherols, Hb haemoglobin, HPLC high performance liquid chromatography, NR not reported, P5P pyridoxal 5 phosphate, PLP pyridoxal 5 phosphate, TDP thiamine diphosphate, TK transketolase, TPP thiamine pyrophosphate …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAGE screen (26) assessed alcohol abuse behaviours; a reference threshold of two or more positive responses established problematic consumption (27, 28). Both measures have previously been used in Czech-speaking populations (29, 30). …”
Section: Materials and Methods Designmentioning
confidence: 99%